The positive effect of JAK inhibitor tofacitinib in the treatment of primary Sjögren’s syndrome: a clinical case - Rekalov, D. H.; Daniuk, I. O.; Рекалов, Дмитро Геннадійович; Данюк, Інна Олександрівна (My University, 2023)
Primary Sjögren’s syndrome (pSS, Sjögren’s disease) is a systemic autoimmune disease which develops in previously healthy individuals and characterized by damage to exocrine glands, mainly lacrimal and salivary glands, with gradual formation of their secretory insufficiency and various systemic manifestations. According to EULAR recommendation (2019) therapeutic management of pSS bases on symptomatic treatment of sicca syndrome and broad-spectrum immunosuppression for systemic manifestations. The perspective group for the treatment of autoimmune disease is Janus kinase inhibitors, which can block the signals from biologically active molecules (interferons, erythropoietins and cytokines) and providing a response to these target cell signals. Therefore, the use of JAK inhibitors in patients with pSS requires clinical confirmation of effectiveness. The article described the clinical case of the positive effect of tofacitinib with methotrexate combination in the treatment of patient with pSS. A 55-year-old female with sicca syndrome (confirmed by Schirmer’s test), arthralgia, low-grade fever, weight loss and a positive test for the detection of specific antibodies (SS-A/Ro > 240 units/ml, SS-B/La 94 units/ml) was diagnosed with pSS. The total score of EULAR Sjögren’s syndrome disease activity index (ESSDAI) was 9 (activity grade II). The treatment included symptomatic methods of sicca syndrome correcting (replacement therapy with artificial tear preparations and chewing gums with xylitol) in combination with immunosuppressive therapy. The addition of tofacitinib 5 mg twice daily to methotrexate (10 mg weekly) has been shown to significantly reduce disease activity after 6 months of treatment (ESSDAI = 0). Первинний синдром Шегрена (пСШ, хвороба Шегрена) — системне автоімунне захворювання, що розвивається в попередньо здорових осіб та характеризується ураженням екзокринних залоз, переважно слізних і слинних, із поступовим формуванням їх секреторної недостатності й різними системними проявами. Згідно з рекомендаціями EULAR (2019), основними методами лікування пСШ є симптоматична терапія проявів сухого синдрому та застосування різних імуносупресивних агентів залежно від конкретного клінічного випадку. Перспективною при лікуванні автоімунних захворювань є група інгібіторів янус-кінази (JAK-інгібіторів), механізм дії яких полягає в блокуванні ферменту янус-кінази, що відповідальна за реакцію клітин-мішеней на зовнішні сигнали від біологічно активних молекул (інтерферони, еритропоетини та цитокіни) і забезпечує протизапальний ефект. Тому дослідження ефективності JAK-інгібіторів у хворих на пСШ є актуальним та потребує клінічного підтвердження. У статті представлено клінічний випадок позитивного впливу тофацитинібу в комбінації з метотрексатом у лікуванні пацієнтки із пСШ. У хворої 55 років із проявами сухого синдрому (підтвердженого пробою Ширмера), артралгією, субфебрилітетом, схудненням та позитивним тестом на специфічні антитіла (SS-A/Ro > 240 ОД/мл, SS-B/La 94 ОД/мл) було діагностовано пСШ. Згідно з індексом ESSDAI (EULAR Sjögren’s syndrome disease activity index), активність хвороби до початку терапії була II ступеня (ESSDAI = 9). Лікування хворої включало симптоматичні методи корекції сухого синдрому (замісна терапія препаратами штучної сльози й жувальні гумки без цукру з ксилітом) та прийом імуносупресивних агентів. Продемонстровано, що додавання тофацитинібу 5 мг двічі на добу до терапії метотрексатом (10 мг щотижня) забезпечувало вірогідне зменшення активності хвороби через 6 місяців лікування (ESSDAІ = 0).
Позитивний ефект JAK-інгібітору тофацитинібу в лікуванні первинного синдрому Шегрена: випадок із клінічної практики
Rekalov D. G. - https://orcid.org/0000-0002- 5793-2322; Daniuk I. O. - https://orcid.org/0000-0002- 4596-5709.
Keywords: primary Sjögren’s syndrome; Janus kinase inhibitor; tofacitinib; clinical case; первинний синдром Шегрена; інгібітори янус-кінази; тофацитиніб; клінічний випадок